Hydroxyisohexyl 3-cyclohexene carboxaldehyde allergy: relationship between patch test and repeated open application test thresholds - Fischer, L.A.; Menné, T.; Avnstorp, C.; Kasting, G.B.; Johansen, J.D. (British journal of dermatology (1951), 2009)
Summary Background  Hydroxyisohexyl 3‐cyclohexene carboxaldehyde (HICC) is a synthetic fragrance ingredient. Case reports of allergy to HICC appeared in the 1980s, and HICC has recently been included in the European baseline series. Human elicitation dose–response studies performed with different allergens have shown a significant relationship between the patch‐test threshold and the repeated open application test (ROAT) threshold, which mimics some real‐life exposure situations. Fragrance ingredients are special as significant amounts of allergen may evaporate from the skin. Objectives  The study aimed to investigate the relationship between elicitation threshold doses at the patch test and the ROAT, using HICC as the allergen. The expected evaporation rate was calculated. Materials and methods  Seventeen HICC‐allergic persons were tested with a dilution series of HICC in a patch test and a ROAT (duration up to 21 days). Seventeen persons with no HICC allergy were included as control group for the ROAT. Results  The response frequency to the ROAT (in μg HICC cm−2 per application) was significantly higher than the response frequency to the patch test at one of the tested doses. Furthermore the response rate to the accumulated ROAT dose was significantly lower at half of the doses compared with the patch test. The evaporation rate of HICC was calculated to be 72% over a 24‐h period. Conclusions  The ROAT threshold in dose per area per application is lower than the patch test threshold; furthermore the accumulated ROAT threshold is higher than the patch test threshold, which can probably be explained by the evaporation of HICC from the skin in the open test.